2016
DOI: 10.1007/s13337-016-0314-z
|View full text |Cite|
|
Sign up to set email alerts
|

Chikungunya: a reemerging infection spreading during 2010 dengue fever outbreak in National Capital Region of India

Abstract: Chikungunya fever is an important reemerging arbovirus illness, which is transmitted by the same vector as of dengue virus. Many cases of concurrent infections with multiple dengue virus serotypes have been reported in many countries. Also, concurrent infection with Chikungunya virus and dengue virus has been reported in the past in Delhi. Therefore, this study was done to detect Chikungunya IgM antibodies in suspected dengue fever patients. In this study, 1666 serum samples suspected of dengue fever and colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…These data are in stark contrast with other studies conducted in the country that have reported the presence of DENV in approximately 30% of patients with febrile syndrome [ 42 ] and a cumulative incidence of cases ranging between 36.5 and 268.7 cases/100,000 inhabitants in different regions of Colombia [ 43 , 44 ]. This low DENV detection rate can be explained by an increase in the number of cases of the other arboviruses studied, as it has been previously reported in India, where the prevalence of DENV decreased with the increase in cases of CHIKV [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 59%
“…These data are in stark contrast with other studies conducted in the country that have reported the presence of DENV in approximately 30% of patients with febrile syndrome [ 42 ] and a cumulative incidence of cases ranging between 36.5 and 268.7 cases/100,000 inhabitants in different regions of Colombia [ 43 , 44 ]. This low DENV detection rate can be explained by an increase in the number of cases of the other arboviruses studied, as it has been previously reported in India, where the prevalence of DENV decreased with the increase in cases of CHIKV [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 59%
“…A large outbreak of Chikungunya was reported in Ahmedabad in India in 2006 [ 22 ]. Sharing the same vector, chikungunya is likely to occur during dengue outbreaks, and in a study during a dengue outbreak in Delhi in 2010, 10% (66/666) positive chikungunya cases were diagnosed among dengue IgM negative fever patients [ 23 ]. Sporadic outbreaks of chikungunya has been reported in India since 1963, in 2006 affecting 13 states with 1.4 million suspected cases [ 23 ], with high numbers in Andhra Pradesh, Tamil Nadu and Maharashtra.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing the same vector, chikungunya is likely to occur during dengue outbreaks, and in a study during a dengue outbreak in Delhi in 2010, 10% (66/666) positive chikungunya cases were diagnosed among dengue IgM negative fever patients [ 23 ]. Sporadic outbreaks of chikungunya has been reported in India since 1963, in 2006 affecting 13 states with 1.4 million suspected cases [ 23 ], with high numbers in Andhra Pradesh, Tamil Nadu and Maharashtra. This supports the finding in the present study of highest prevalence of chikungunya in Anantapur (Andhra Pradesh), Oddanchatram and Ambur (Tamil Nadu) and Ratnagiri (Maharashtra).…”
Section: Discussionmentioning
confidence: 99%
“…In India, first outbreak occurred in Kolkata in 1963, since then a number of other outbreaks in Maharashtra, Andhra [10]. In 2010, the National Capital Region of India was the seroprevalence rate 9.91% [11]. In 2016, Mumbai reported 12.5% seroprevalence rate [12].…”
Section: Introductionmentioning
confidence: 99%